Von Sternberg - Baxter, John, 1939- (Screen classics (Lexington, Ky.), 2010)
Belligerent and evasive, Josef von Sternberg chose to ignore his illegitimate birth in Austria, deprived New York childhood, abusive father, and lack of education. The director who strutted onto the set in a turban, riding breeches, or a silk robe embraced his new persona as a world traveller, collected modern art, drove a Rolls Royce, and earned three times as much as the president. Von Sternberg traces the choices that carried the unique director from poverty in Vienna to power in Hollywood, including his eventual ostracism in Japan. Historian John Baxter reveals an artist few people knew.